Andrographis paniculata (Burm.f) Wall. ex Ness: a potent antibacterial plant - Ahmed, Qamar Uddin; Abd. Samah, Othman; Sule, Abubakar (InTech - Open Access Publisher, University Campus STeP Ri, Slavka Krautzeka 83/A, 51000 Rijeka, Croatia, 2012)
Antibacterial agents of plant origin have vast therapeutic potential. They are valuable in the treatment of infectious diseases while simultaneously extenuating many of the side effects that are often associated with synthetic antibacterial agents. The beneficial medicinal effects of plant materials typically result from the combinations of secondary metabolites such as alkaloids, steroids, tannins, phenol compounds, flavonoids and resins fatty acids gums which are capable of producing definite physiological action on body (Paul et al., 2006). Nowadays, multiple drug resistance has developed due to indiscriminate use of commercial antimicrobial drugs commonly used in the treatment of infectious disease. In addition to this problem, antibiotics are sometimes associated with adverse side effects on the host including hypersensitivity, immune-suppression and allergic reactions. This situation forced scientists to search for new antimicrobial substances. Giving the alarming incidence of antibiotic resistance in bacteria of medical importance, there is a constant need for new and effective therapeutic agents. Therefore, there is a need to develop alternative antimicrobial drugs for the treatment of infectious diseases from medicinal plants. Biodiversity is a precious source for modern biotechnology. It is a source which potentially holds innovative and sustainable solutions to a broad range of important problems for modern society. Improved cooperation between the natural product chemists and the microbiologists is a productive step to speed up the process of evaluating these potentialities. Moreover, microbiologists and natural product chemists in tropical countries, with the richest flora and fauna placed right at their door step have a very central position. They are essential for building up international scientific cooperation, with the objective of expanding our understanding of biological and biochemical diversity, and based on this bringing forward more biological solutions. The entire process is built on a principle of fairness and equity in sharing of the benefits and respecting the State's sovereign right to its own resources. After figuring out the chemical structures of secondary metabolites, it is considered crucial to know how useful these molecules might be in terms of medicinal properties. During the past 40 years, numerous novel compounds have been isolated from different plants and marine organisms and many of these have been reported to have core biological activities, some of which are of interest from the point of view of potential drug development (Lene, 1996; Gerald, 2001). Antimicrobial Agents 346 In this context, Andrographis paniculata (Burm.f.) Wall. ex Nees., could be a potential source to develop new efficacious antibacterial drugs. A. paniculata (Acanthaceae) (King of Bitters) is an annual herbaceous plant and is widely cultivated and traditionally used in Southern Asia, China and some parts of Europe. A. paniculata has been effectively used in traditional Asian medicines for centuries. In traditional medicine, A. paniculata is widely used to get rid of a body heat, dispel toxins from the body, prevents common cold, upper respiratory tract infections including sinusitis and fever (Gabrielian et al., 2002) and as an antidote against snakes and insects poisons (Samy et al., 2008). A. paniculata has been reported to exhibit various mode of biological activities in vivo as well as in vitro viz., antiviral (Wiart et al., 2000), anti-inflammatory (Wen et al., 2010), antihuman immunodeficiency virus (HIV) (Calabrese et al., 2000), immunomodulating/immunostimulatory (Iruretagoyena et al., 2005), anticancer activity (Li et al., 2007; Geethangili et al., 2008) and antibacterial activity.